Facilitation of Auditory Comprehension After Theta Burst Stimulation of Wernicke's Area in Stroke Patients: A Pilot Study - Versace, Viviana; Schwenker, Kerstin; Langthaler, Patrick B.; Golaszewski, Stefan; Sebastianelli, Luca; Brigo, Francesco; Pucks-Faes, Elke; Saltuari, Leopold; Nardone, Raffaele (Frontiers in Neurology, 2020)
Introduction: Single-pulse transcranial magnetic stimulation (TMS) and high frequency repetitive TMS (rTMS) over Wernicke’s area were found to facilitate language functions in right-handed healthy subjects. We aimed at investigating the effects of excitatory rTMS, given as intermittent theta burst stimulation (iTBS) over left Wernicke’s area, on auditory comprehension in patients suffering from fluent aphasia after stroke of the left temporal lobe. Methods: We studied 13 patients with chronic fluent aphasia after an ischemic stroke involving Wernicke's area. iTBS was applied in random order to Wernicke’s area, the right-hemisphere homologous of Wernicke’s area, and the primary visual cortex. Auditory comprehension was blind assessed using the Token Test before (T0), 5 (T1) and 40 minutes (T2) after a single session of iTBS. Results: At the first evaluation (T1) after iTBS on left Wernike’s area, but not on the contralateral homologous area nor on the primary visual cortex, the scores on the Token test were significantly increased. No significant effects were observed at T2. Conclusion: We demonstrated that a single session of excitatory iTBS over Wernicke’s area was safe and led to a transient facilitation of auditory comprehension in chronic stroke patients with lesions in the same area. Further studies are needed to establish whether TBS-induced modulation can be enhanced and transformed into longer-lasting effects by means of repeated TBS sessions and by combining TBS with speech and language therapy.